Cross-organisational Communities of Practice: Enhancing creativity and epistemic cognition in higher education - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando (My University, 2021)
The purpose of this work is to investigate the impact of participation in cross-organisational Communities of Practice (CoPs) on higher education learners studying Design, and specifically the ways in which CoPs can affect their creative outcomes and perceived epistemic cognition. CoPs are social groups that share common interests and goals in a particular field, and interact to build relevant knowledge and expertise. Cross-organisational CoPs can include members from diverse spheres, such as education and industry. Research on the design, implementation and evaluation of this type of CoP in HE remains limited. Findings from this study indicate that CoPs can have significant positive effects on student knowledge gains, creative outcomes and perceptions of epistemic cognition. Key motivators triggering positive epistemic effects in learners included: authentic exchanges and interactions with members of the CoP, such as industry experts; creative constraints; prospective audiences for the end-products; and the potential impact on their future careers.
Keywords: Bridging education and industry; Creativity; Communities of practice; Epistemic cognition